Developing a Rational, Optimized Product of Centella asiatica for Examination in Clinical Trials: Real World Challenges - Wright, Kirsten M.; McFerrin, Janis; Alcázar Magaña, Armando; Roberts, Joanne; Caruso, Maya; Kretzschmar, Doris; Stevens, Jan F.; Maier, Claudia S.; Quinn, Joseph F.; Soumyanath, Amala (Frontiers in Nutrition, 2022)
Botanical products are frequently sold as dietary supplements and their use by the public is increasing in popularity. However, the scientific evaluation of their medicinal benefits presents unique challenges due to their chemical complexity, inherent variability, and the involvement of multiple active components and biological targets. Translation away from preclinical models, and developing an optimized, reproducible botanical product for use in clinical trials, presents particular challenges for phytotherapeutic agents compared to single chemical entities. Common deficiencies noted in clinical trials of botanical products include limited characterization of the product tested, inadequate placebo control, and lack of rationale for the type of product tested, dose used, outcome measures or even the study population. Our group has focused on Centella asiatica, an Eastern Medicine botanical, due to its reputation for enhancing cognition. Our preclinical studies on a Centella asiatica water extract (CAW) and its bioactive components strongly support its potential as a phytotherapeutic agent for cognitive decline in aging and Alzheimer’s disease through influences on antioxidant response, mitochondrial activity, and synaptic density. Here we describe our robust, scientific approach towards developing a rational phytotherapeutic product based on Centella asiatica for human investigation, addressing multiple factors to optimize its valid clinical evaluation. Specific aspects covered include approaches to identifying an optimal dose range for clinical assessment, design and composition of a dosage form and matching placebo, sourcing appropriate botanical raw material for product manufacture (including the evaluation of active compounds and contaminants), and up-scaling of laboratory extraction methods to available Current Good Manufacturing Practice (cGMP) certified industrial facilities. We also address the process of obtaining regulatory approvals to proceed with clinical trials. Our study highlights the complexity of translational research on botanicals and the importance of identifying active compounds and developing sound analytical and bioanalytical methods for their determination in botanical materials and biological samples. Recent Phase I pharmacokinetic studies of our Centella asiatica product in humans (NCT03929250, NCT03937908) have highlighted additional challenges associated with designing botanical bioavailability studies, including specific dietary considerations that need to be considered.